Retrospective analysis of group tactical actions in defense when receiving a serve in volleyball - Savelyev, T.A.; Ananin А.S. (Theory and Practice of Physical Culture, 2026)
Due to changes in the rules, coaches of high-level teams are developing new tactical options. However, these options have no scientific basis and are not used in the long-term training system of volleyball players. A contradiction arises. On one hand, there is a practical need to improve the training system. On the other hand, there is no understanding of how volleyball tactics will develop. The aim of the study is to determine the trends in the development of group tactical actions in defense when receiving a serve based on a retrospective analysis.